2022
DOI: 10.1021/acscatal.2c02612
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Screening Accelerates the Discovery of Rhodium Catalyst Systems for Selective Intra- and Intermolecular C–H Amidations

Abstract: We report herein a series of tailored CpXRh­(LX)Cl catalyst systems for the outer-sphere C–H amidations discovered by high-throughput experimentation. Using a diverse repertoire of Cp-tunable group 9 [CpXMCl2]2 precatalysts in combination with bidentate LX-type co-ligands, we have established a premixing protocol for the fast and convenient in situ generation of an array of half-sandwich metal complexes. Benefitting from the designed multidimensional approach to simultaneously screen the metal center, CpX, LX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 114 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…Recently, the Chang group established a high-throughput experimentation (HTE) approach to quickly identify the optimal reaction parameters for outer-sphere C–H amidation reactions (Scheme 5). 22 With this approach, they soon identified that Cp X Rh(LX) bearing a bidentate LX-type co-ligand were effective catalysts for intra- and intermolecular C–H amination reactions by utilizing N -tosyloxycarbamates as nitrenoid sources. Moreover, this parallel screening approach enabled a quick identification of a chiral catalyst with l -prolinamide as a ligand for asymmetric C–H amidation.…”
Section: Hydroxylamide-derived Acyl Nitrene Precursorsmentioning
confidence: 99%
“…Recently, the Chang group established a high-throughput experimentation (HTE) approach to quickly identify the optimal reaction parameters for outer-sphere C–H amidation reactions (Scheme 5). 22 With this approach, they soon identified that Cp X Rh(LX) bearing a bidentate LX-type co-ligand were effective catalysts for intra- and intermolecular C–H amination reactions by utilizing N -tosyloxycarbamates as nitrenoid sources. Moreover, this parallel screening approach enabled a quick identification of a chiral catalyst with l -prolinamide as a ligand for asymmetric C–H amidation.…”
Section: Hydroxylamide-derived Acyl Nitrene Precursorsmentioning
confidence: 99%
“…Intramolecular C(sp 3 )–H amination methods can lead to valuable changes in site- and chemo-selectivity compared to intermolecular variants. 12–14 Nonetheless, intermolecular reactions often place less restrictions on the substrates than intramolecular reactions and thus have more potential for generality and late-stage functionalization. Hence, we will focus on intermolecular enantioselective C(sp 3 )–H amination reactions rather than intramolecular reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,2‐dioxazol‐5‐ones have been successfully engaged as N ‐donor sources in C−H amidation reactions (including stereo‐ and enantioselective variants) to access pharmaceutically relevant N ‐aryl amides, oxazoles, and lactams [6] . Such transformations have been realised via inner‐sphere mechanisms involving strongly‐ or weakly‐coordinating directing groups [7] and outer‐sphere mechanisms [5b, 6b, 8] …”
Section: Introductionmentioning
confidence: 99%